RELACIONES OBJETALES, TRASTORNOS DE LA PERSONALIDAD Y DROGODEPENDENCIA - Palacio Pérez, Andrés Felipe (Universidad de Costa Rica, 2023)
This article exposes the relationship between personality disorders and drugdependence, including some forms of addiction. For this purpose, the PsychoanalyticTheory of Object Relations will be used, in order to establish an explanation of the rolethat this symptomatology plays in these psychopathological structures. All this will beaddressed as a contribution to understanding the relationship between symptoms andcharacter structure in the constitution of personality disorders, and as a contribution tothe psychodynamic clinic and intervention of addictions.